Лирический текст и коммуникативная структура предложения: о ее композиционно-организующей роли в трех стихотворениях О. Э. Мандельштама - Zel′dovič, Gennadij (Wiener Slawistischer Almanach, 2024)
The paper demonstrates that, along with its standard function of linking the relevant utterance to the context, information structure (whose main parameters are assumed to be theme-rheme division, given-new division, and direct vs. inverted word order contrast) may also fulfil a more intricate role in lyrical text. First, the function of information structure may be extended to mark the inner discourse hierarchization of the poem, i. e. its division into backgrounded part (where some experience open to the lyrical hero is presented), and foregrounded, ‘wisdom’ part (where discovery of some important, mostly general truth is made). Second, at the level of information structure, the evolution of lyrical text may enter into iconic or quasi-iconic correspondence with its explicit content. This is shown with reference to three famous poems by O. Mandelstam. The final conclusion is that, in the general case, true functions of information structure stretch far beyond what is claimed in the standard, ‘non-poetically-oriented’ literature on the subject.